KONSEP TAMAN PEKARANGAN SEBAGAI ZONA TERAPI DAN EDUKASI BAGI ANAK AUTIS (STUDI KASUS : SEKOLAH LUAR BIASA (SLB) SUMBER DHARMA MALANG) - Irawan Setyabudi; Wahidyanti Rahayu Hastutiningtyas (http://arl.faperta.ipb.ac.id/, 2017)
Architecture in space-making is not only for normal people but also adapted for people with disabilities need, for example : people with mentally disabled or autistic. Children with autism have disturbances about sensory system that failed to respond and are not adaptive to their environment. As a therapy facility, outdoor space should be involved to stimulate the senses or sensory, besides functioning for recreation, ecological, and aesthetic. It became the basic concept of the sensory garden. Generally, the space required is quite extensive because it includes a lot of special zones for the garden that stimuli visual, hearing, touch, smell, and taste. but there is a tendency to be a challenge of limited space architects in preparing the organization of space. The case study was conducted at a school that has a limited space, that is school for disabilities (SLB) Sumber Dharma Malang. In existing conditions, there were plants, pavement, and play areas are not arranged so it makes the urgency for the garden arrangement. Qualitative research methods implemented by the architectural design with the approach of agricultural science and health. The purpose of this study is to provide an alternative concept as a recommendation to accommodate the design capable of autistic children ranging from kindergarten to high school. The conclusion of this study is the concept of gardening landscape. It is not only functioned as an aesthetic part but also as the therapy facility for all children age level in a particular zone.